Pengaruh Motivasi Belajar dan Kompetensi Dosen terhadap Perolehan IPK Mahasiswa Akuntansi UIN Syarif Hidayatullah Jakarta - Mutiara Intan Wahyuni; Zahra Ananda Putri (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
Continuing education to the Bachelor's degree is indeed voluntary, but various fields of work currently prefer job candidates who have an Bachelor's degree. Based on the results of observations, there are still many people who are indifferent to the 12-year compulsory education regulations and pursue education up to a Bachelor's degree. The internal factor that influences the success of learning is learning motivation, while the external factor that affects the acquisition of student GPA is lecturer performance. The purpose of this study was to determine the effect of learning motivation and lecturer competence on GPA acquisition of accounting students at Uin Syarif Hidayatullah Jakarta. The method used is descriptive method with a qualitative approach, with the population being students of the Accounting study program, the research data is presented based on the results of a questionnaire. The data obtained through the questionnaire was then used as a reference to be processed and analyzed using the help of the Statistical Package for the Social Sciences (SPSS) 29 to obtain results that could support this research. The results of this study concluded that learning motivation (X1) had no significant effect on the acquisition of GPA for accounting students at UIN Syarif Hidayatullah Jakarta, lecturer competence (X2) had a significant effect on the acquisition of GPA for accounting students at UIN Syarif Hidayatullah Jakarta, and learning motivation (X1) and lecturer competence (X2) has a simultaneous effect on the acquisition of GPA for accounting students at UIN Syarif Hidayatullah Jakarta